Changes in microchip position after implantation of a subretinal vision prosthesis in humans. Issue 6 (28th February 2019) - Kuehlewein, Laura; Troelenberg, Nicole; Stingl, Krunoslav; Schleehauf, Sebastian; Kusnyerik, Akos; Jackson, Timothy L.; MacLaren, Robert E.; Chee, Caroline; Roider, Johann; Wilhelm, Barbara; Gekeler, Florian; Bartz‐Schmidt, Karl Ulrich; et al.
Abstract: Purpose: Retinal prosthetic devices have been developed to partially restore very low vision in legally blind patients with end‐stage hereditary retinal dystrophies. Subretinal implants, unlike epiretinal implants, are not fixated by a tack. The aim of this study was to assess and analyse possible changes over time in the subretinal position of the RETINA IMPLANT Alpha IMS and Alpha AMS (ClinicalTrials.gov NCT01024803). Methods: Imaging studies were performed on fundus photographs using GIMP (Version 2.8.14). Postoperative photographs of the implanted eye were scaled and aligned. Landmarks were chosen and distances between landmarks were measured to then calculate the displacement of the microchip using a transformation matrix for rotational and translational movements. Analyses were performed using MATLAB 8.6 (The MathWorks Inc., Natick, MA). Results: Of the 27 datasets with the Alpha IMS device, 12 (44%) remained stable without displacement of the microchip relative to the optic disc and the major blood vessels, whereas in 15 (56%), displacement occurred. The mean ± SD displacement in those 15 eyes was 0.66 ± 0.35 mm (range, 0.24–1.67 mm). Of the eight datasets with the Alpha AMS device, 1 (13%) remained stable without displacement of the microchip relative to the optic disc and the major blood vessels, whereas in 7 (87%), displacement occurred. The mean ± SD displacement in those seven eyes was 0.66 ± 0.26 mm (range, 0.32–0.97 mm). Calculated from all eyes (including those in which no displacement occurred), the mean displacement was 0.36 mm in the IMS cohort, and 0.58 mm in the AMS cohort, however, the difference was not statistically significant (p = 0.17). Conclusions: We have shown that the position of the subretinal implant changes in the majority of the cases after implantation. While the overall mean displacement of the chip was not significantly different in either of the cohorts, the maximum displacement was smaller in the Alpha AMS cohort.